Determinants of Youth Unemployment in the Democratic Republic of Congo: An Empirical Analysis from 2001-2020 - Nakuno BALEMBA, (International Journal of Scientific Research and Management (IJSRM), 2022)
This article examines the determinants of unemployment in the DRC. The reduced nature of the sample, namely one country, is explained by the availability of data covering the period 2001-2020.The model inspired by the empirical literature is estimated by the ordinary least squares (OLS) method. After estimates by the OLS method, our econometric results reveal that the variables education, inflation, direct investment abroad, the population significantly explain the level of youth unemployment at the threshold of 1% and 5%. Education and foreign direct investment tend to increase the unemployment rate while population growth and inflation tend to reduce the unemployment rate. Our analysis of the determinants of unemployment appears to contribute to the literature on several levels. First, because few studies exist on the subject in the Democratic Republic of Congo. Compared to existing work, our study goes beyond methodologically by relying on more robust techniques such as ordinary least squares (OLS) and instrumental variables. Finally, the article will serve as an interpellation and awakening of the consciences of political actors on the intolerable degree of unemployment in the context of the DRC, and will refer to it when necessary in political or economic decision-making.